PENARAPAN BALANCED SCORECARD DALAM PENCAPAIAN VISI DAN MISI PADA SMA IPIEMS SURABAYA - Pranata, Muhamad Joni; Idayati, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to measure how the performance of Ipiems Senior High School Surabaya is by using Balanced Scorecard method which is based on the 4 perspectives, so it is can support the Ipiems Senior High School Surabaya in achieving its mission and vision. Based on the analysis which has carried out in the year of 2010/2011 until 2010/2013, it can be found that: (1) Financial perspective is increase and Cost Efficiency, but which is decrease in the Increase Revenue. (2) Customersâ perspective is well enough in the Ipiems Senior High School Surabaya with the increase of the Service Excellence, Price, and Availlibility. (3) Internal Business perspektive increase to Space Management and Operational Excellence but the Public Relations should decrease in one cooperation in the year of 2012/2013. (4) The perspective of growth and learning is well enough by means of solve the customersâ complaint, as well as the consictency of the competency and skill in the numbers of 100%, nevertheless the motivation decrease of 9.25%, in the culture which is well enough with the complementary each of the employee, in the information system is already carried out well enough by means of email as the the instrument of long distance communication media.Keywords: Performance,Balanced Scorecard, Vision and Mission.